Effects of computer mouse control-display gain on upper extremity muscle fatigue, subjective fatigue and user performance. - Ren, Yihui; Gou, Bingchen; Chen, Ruiqi; Gan, Yihan; Wang, Mengcheng; Jiang, Ao; Shi, Jinlei; Fan, Hao (Work, 2025)
Background: Operating a mouse for long periods of time increases the risk of muscle fatigue in the upper limbs of office workers. Objective: This study aimed to contribute to the field of knowledge by providing guidance on the selection of a suitable computer mouse control-display gain (CDG) for office workers, and to reduce muscle fatigue and fatigue accumulation in office workers who use computer mice. Method: Thirty healthy office workers used five different control-display gain settings to complete five sessions of a 30-min Fitts' task. Muscle activity in the extensor digitorum, extensor carpi ulnaris and flexor digitorum superficialis were measured by surface electromyography (sEMG). Subjective muscle fatigue was assessed using the Borg Rating Scale and user performance was recorded using the GoFitts program. Results: It was found that when the control-display gain was set to 12.97, the highest effective frequency of operation was reached by the users. Additionally, the subjects reported more subjective muscle fatigue at a control-display gain of 12.97, and the sEMG data showed that manipulation led to more upper limb muscle fatigue when the control-display gain was set to 8.64 and 12.97. Upper limb muscle fatigue, subjective muscle fatigue and user performance also varied between genders. Overall, female subjects had lower error rates while male subjects reported higher levels of subjective muscle fatigue and were more adaptable to the low control-display gain setting. Conclusion: This study found a correlation between muscle fatigue and subjective fatigue with control-display gain. Similar to the subjective fatigue for control-display gain settings, the control-display gain settings that are commonly used by office workers may lead to higher levels of fatigue in the forearm muscles. This study could provide guidance for the selection of computer mouse control-display gain to reduce muscle fatigue and fatigue accumulation in office workers who use computer mice.